Preferensi Konsumen Terhadap Layanan M-banking : Studi Kasus Pada Bank NTT - Dosince M. Metkono; Fransina W. Ballo; Cicilia A. Tungga (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Technological developments have had a huge impact on the banking system, one example of the impact of developments is increasingly modern payment systems such as mobile banking. Bank NTT is one of the banks that provides mobile banking services called B'pung mobile. This research aims to determine consumer preferences for mobile banking services at Bank NTT. This research uses a qualitative descriptive approach, by conducting structured interviews with informants and NTT bank customers. The research results show that consumer preferences for mobile banking services at NTT banks continue to experience positive developments in line with technological advances and changes in user behavior, ease of access, transaction security, feature and functional innovations are getting better. However, in its implementation there are several problems, namely a weak internet connection, no fingerprint feature and also a top up feature that is difficult to access.